Target estimation and adjustment weighting for survey nonresponse and sampling bias - Caughey, Devin ca. 20./21. Jh; Berinsky, Adam J. 1970-; Chatfield, Sara ca. 20./21. Jh; Hartman, Erin ca. 20./21. Jh; Schickler, Eric 1969-; Sekhon, Jasjeet Singh 1971- (Cambridge University Press, 2020)
We elaborate a general workflow of weighting-based survey inference, decomposing it into two main tasks. The first is the estimation of population targets from one or more sources of auxiliary information. The second is the construction of weights that calibrate the survey sample to the population targets. We emphasize that these tasks are predicated on models of the measurement, sampling, and nonresponse process whose assumptions cannot be fully tested. After describing this workflow in abstract terms, we then describe in detail how it can be applied to the analysis of historical and contemporary opinion polls. We also discuss extensions of the basic workflow, particularly inference for causal quantities and multilevel regression and poststratification
Title from publisher's bibliographic system (viewed on 07 Oct 2020)
Keywords: Sampling (Statistics); Inference; Estimation theory; Aufsatzsammlung